Phytochemical and biological investigation on Artocarpus chaplasha Roxb - Sharmin, Sanjida; Tareq, Fakir Shahidullah; Hasan, Choudhury Mahmood; Ahsan, Monira (IIUC Studies, 2018)
The methanolic extract of the stem bark of Artocarpus chaplasha Roxb. (Family: Moraceae) was investigated for the isolation of pure compounds and determination of few biological activities. A mixture of two compounds cycloartenyl acetate and lupeol acetate were isolated from it. The crude methanol extract as well as its petroleum ether, chloroform, carbon tetrachloride and aqueous soluble fractions were studied for antioxidant, cytotoxic and antimicrobial activities. Among the different fractions, the aqueous soluble partitionate was found to have most potent antioxidant activity as compared to tertbutyl-1- hydroxytoluene. Antimicrobial screening of the different fractions was performed using the disc diffusion method. In these tests, the chloroform soluble fraction and carbon tetrachloride soluble fraction of methanolic extract exhibited moderate antimicrobial activity (range of zone of inhibition 8-12 mm). In brine shrimp lethality test, the petroleum ether soluble extract exhibited the highest level of cytotoxicity. IIUC Studies Vol.14(1) June 2017: 45-52